2015
DOI: 10.1007/s12599-015-0379-z
|View full text |Cite
|
Sign up to set email alerts
|

Connect Me! Antecedents and Impact of Social Connectedness in Enterprise Social Software

Abstract: Companies are increasingly adopting social software to support collaboration and networking. Although increasing their employees' connectedness is a major driver for organizations to deploy enterprise social software (ESS), the social connectedness concept itself is still not sufficiently defined and conceptualized. The study therefore provides a richer perspective on social connectedness's role in an ESS context. The authors thus investigate (1) social connectedness's antecedents and (2) its impact on employe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 132 publications
(153 reference statements)
1
26
0
Order By: Relevance
“…A change in the communication structure can radiate into various areas of the organisation [3]. Further examination of the interplay between cultural factors and ESN therefore is desirable [12].…”
Section: Cultural Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…A change in the communication structure can radiate into various areas of the organisation [3]. Further examination of the interplay between cultural factors and ESN therefore is desirable [12].…”
Section: Cultural Effectsmentioning
confidence: 99%
“…ESN have been found to support coordination in respect of work shared between employees within organisations by for example providing functions that help employees to fulfil subtasks [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…lacking a temporal view accounting for how outcomes and benefits actually evolve, e.g. [23,24,28,34,40,78,89,94]. In this study, we address this limitation; our aim is to investigate and understand how enterprise collaboration platform outcomes and benefits change over time.…”
Section: Introductionmentioning
confidence: 99%
“…Social connectedness is a vital ingredient of the acceptance by others (a significant predictor of resilience) and can be fostered through positive interpersonal relationship (Lee et al, 2017). Research in 2015 found a positive relation between social connectedness with the reputation of an employee (Kügler et al, 2015). As social support is essential in working space (research laboratory, office, library, etc.…”
Section: Introductionmentioning
confidence: 99%